Darah Sebagai Komponen Vital Integrasi Tafsir Al-Qur’an dengan Pengatahuan Sains Tentang Sistem Peredaran Darah - Siti Aisah; Siti Aminah; Taufik Warman Mahfuzh (Jurnal Tafsere, 2024)
Blood is one of the most important cellular components of the human body created by Allah SWT. Several verses in the Qur'an explain the importance of blood and the circulatory system in the human body. This concept is also consistent with the findings of modern science, which discusses the importance of blood and its circulatory system. The purpose of this study is to explore the importance of blood and the circulatory system in the human body according to the Qur'an and modern science. The results show that there is an important connection between the explanation of blood in the Qur'an and the findings of modern science on the importance of blood and the cardiovascular system in the human body.